Audit Sistem Informasi Kesiman Kertalangu (SIKEKAL) Menggunakan COBIT 4.1 - Mulyawan, Made Dwi; Hartati, Rukmi Sari; Divayana, Yoga (Majalah Ilmiah Teknologi Elektro; Vol 19 No 2 (2020): (Juli - Desember) Majalah Ilmiah Teknologi ElektroDO - 10.24843/MITE.2020.v19i02.P03, 2020)
Information System of Kesiman Kertalangu (SIKEKAL) is a system implemented in the Kesiman Kertalangu Village as a solution to facilitate the accommodation of population administration services. To measure and evaluate the performance of the system used it is necessary to conduct an audit using the COBIT 4.1 framework, which in this case is focused on measuring the maturity level of the SIKEKAL system based on aspects of the DS (Delivery and Support) domain, especially in the subdomains of DS5, DS10, DS11, and DS13. This evaluation process also aims to provide recommendations for problems found in the system to be able to be improved in achieving the maturity target to be achieved by the Kesiman Kertalangu Village Office.